The Influence of Information Technology, the Web, and Knowledge on Information Systems - Endah Sabarini, Nur; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The Influence of Information Technology, Web, and Knowledge on Information Systems is a literature review focusing on the ESSB field. The purpose of this paper is to develop hypotheses regarding the correlation between variables that will serve as the foundation for future research. The method applied in this study is literature analysis using electronic sources such as e-books and publicly available journals. The analytical approach used is qualitative descriptive. Here are the findings from this analysis: (1) Information Technology influences Information Systems; (2) Web influences Information Systems; (3) Knowledge influences Information Systems.